Cuneiform Texts from Babylonian Tablets in the British Museum. Part XXIV. Copies and descriptions by L. W. King - Budge, Ernest A. Wallis (1967)
First published by the Trustees of the British Museum, London (1908). Photolithographic Reprint 1967.